Discovery of a cytochrome P450 enzyme catalyzing the formation of spirooxindole alkaloid scaffold - Nguyen, Tuan-Anh M.; Grzech, Dagny; Chung, Khoa; Xia, Zhicheng; Nguyen, Trinh-Don; Dang, Thu-Thuy T. (Frontiers in Plant Science, 2023)
Spirooxindole alkaloids feature a unique scaffold of an oxindole ring sharing an atom with a heterocyclic moiety. These compounds display an extensive range of biological activities such as anticancer, antibiotics, and anti-hypertension. Despite their structural and functional significance, the establishment and rationale of the spirooxindole scaffold biosynthesis are yet to be elucidated. Herein, we report the discovery and characterization of a cytochrome P450 enzyme from kratom (Mitragyna speciosa) responsible for the formation of the spirooxindole alkaloids 3-epi-corynoxeine (3R, 7R) and isocorynoxeine (3S, 7S) from the corynanthe-type (3R)-secoyohimbane precursors. Expression of the newly discovered enzyme in Saccharomyces cerevisiae yeast allows for the efficient in vivo and in vitro production of spirooxindoles. This discovery highlights the versatility of plant cytochrome P450 enzymes in building unusual alkaloid scaffolds and opens a gateway to access the prestigious spirooxindole pharmacophore and its derivatives.